Про розв’язнiсть диференцiально-операторних включень II порядку з некоерцитивними операторами Wλo-псевдомонотонного типу - Задоянчук, Н.В.; Касьянов, П.О. (Видавничий дім "Академперіодика" НАН України, 2008)
We consider the second-order differential-operator inclusions with operators of the pseudomonotone type. The existence of solutions for the Cauchy problem for such inclusions by using the singular perturbation method is justified. The important a priori estimates have been obtained. An example that illustrates the given result is presented.